Análisis de las implicaciones de la modalidad de estudio híbrida “distancia-virtual” en el cantón Bolívar, durante la pandemia COVID-19 período 2020 - Andrade Román, Gianna Emilia (2022)
This curricular integration work aims to analyze the implications of the distance-virtual hybrid study modality in Bolívar canton, during the Covid-19 pandemic period 2020, for the economic and social improvement of the inhabitants. For this they established scientific theories that provided a theoretical support to the research, as well as scientific methods such as synthetic analytical, inductive and deductive that allowed efficient development, where it was possible to verify the impact of the health emergency on the community, it was also diagnosed through a survey the current situation in Bolívar canton during the pandemic and how they economically supported their homes. Subsequently, the indicators were defined using economic and social development as variables. From the economic aspect it was determined: poverty level 40% affected, unemployment 59% increase, economic growth decreased by 84%, and economic activity fell to 82%. From the social point of view, it was found: social welfare was shown at 37%, the health and well-being parameter increased to 87%, the level of education fell to 87%, the living condition was set at 39% and finally education was affected by 39%, demonstrating that the implications were of an economic nature, social, labor and educational. Finally, an action plan was proposed where strategies, objectives and activities were established, all focused on mitigating the implications of the hybrid distance-virtual study modality in order to improve the economic and social situation of the inhabitants during the Covid-19 pandemic.